Epigenetically altered miR‐193b targets cyclin D1 in prostate cancer. (1st July 2015) - Kaukoniemi, Kirsi M.; Rauhala, Hanna E.; Scaravilli, Mauro; Latonen, Leena; Annala, Matti; Vessella, Robert L.; Nykter, Matti; Tammela, Teuvo L. J.; Visakorpi, Tapio
Abstract Micro‐RNAs (miRNA) are important regulators of gene expression and often differentially expressed in cancer and other diseases. We have previously shown that miR‐193b is hypermethylated in prostate cancer (PC) and suppresses cell growth. It has been suggested that miR‐193b targets cyclin D1 in several malignancies. Here, our aim was to determine if miR‐193b targets cyclin D1 in prostate cancer. Our data show that miR‐193b is commonly methylated in PC samples compared to benign prostate hyperplasia. We found reduced miR‐193b expression (P < 0.05) in stage pT3 tumors compared to pT2 tumors in a cohort of prostatectomy specimens. In 22Rv1 PC cells with low endogenous miR‐193b expression, the overexpression of miR‐193b reduced CCND1 mRNA levels and cyclin D1 protein levels. In addition, the exogenous expression of miR‐193b decreased the phosphorylation level of RB, a target of the cyclin D1‐CDK4/6 pathway. Moreover, according to a reporter assay, miR‐193b targeted the 3'UTR of CCND1 in PC cells and the CCND1 activity was rescued by expressing CCND1 lacking its 3'UTR. Immunohistochemical analysis of cyclin D1 showed that castration‐resistant prostate cancers have significantly (P = 0.0237) higher expression of cyclin D1 compared to hormone‐naïve cases. Furthermore, the PC cell lines 22Rv1 and VCaP, which express low levels of miR‐193b and high levels of CCND1, showed significant growth retardation when treated with a CDK4/6 inhibitor. In contrast, the inhibitor had no effect on the growth of PC‐3 and DU145 cells with high miR‐193b and low CCND1 expression. Taken together, our data demonstrate that miR‐193b targets cyclin D1 in prostate cancer.